Human Gut Microbiota and Parkinson's Disease in an Egyptian Population - Hashish, Sara (AUC Knowledge Fountain, 2023)
Multiple lines of evidence suggest the role of the gut microbiome in the predisposition and progression of Parkinson’s disease. This present cross-sectional study was performed to compare the composition of the gastrointestinal microbiota in patients with Parkinson's disease to their counterparts. Stringent inclusion criteria were followed to reliably identify our target population. Parkinson’s patients (n = 40) along with reference subjects (n = 39) were recruited from November 2021 to August 2022. Detailed demographic and clinical data were obtained at baseline using a set of questionnaires and clinical assessment tools. Fecal specimens were collected from all participants, and gut commensals were characterized using 16S rRNA gene amplicon sequencing. The endpoint was to discern the disparities in the gut microbiota structure. Our results demonstrate no significant difference at the taxonomic level between Parkinson's patients and the reference group. However, marginally significant species associated with intestinal inflammation, gut permeability, and mitochondrial dysfunction were reported. These recent findings create an opportunity for further studies comprising a bigger sample size and using higher resolution sequencing techniques in aims to better understand whether and to what extent gut microbiota alterations play a role in the disease pathogenesis.